2022
DOI: 10.1039/d2cp03350j
|View full text |Cite
|
Sign up to set email alerts
|

Tunability of the electronic properties and electrical contact in graphene/SiH heterostructures

Abstract: Stacking different two-dimensional materials to generate vertical heterostructure has been considered as a promising way to obtain desired properties and improve the device's performance. Here, in this work, using first...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…There are currently extensive experimental and theoretical efforts to investigate van der Waals (vdW) heterostructures and their Schottky barrier heights. [34][35][36][37] And the contact barrier of this heterostructure can usually be adjusted by applying external electric fields and other methods to achieve ideal contact.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently extensive experimental and theoretical efforts to investigate van der Waals (vdW) heterostructures and their Schottky barrier heights. [34][35][36][37] And the contact barrier of this heterostructure can usually be adjusted by applying external electric fields and other methods to achieve ideal contact.…”
Section: Introductionmentioning
confidence: 99%
“…26) and so forth. [27][28][29][30] Recently, a groundbreaking experimental synthesis of a novel metallic monolayer, known as MoSH, has been reported. 31 Similar to graphene, the Janus MoSH monolayer exhibits metallic properties and possesses a high intrinsic carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that these heterostructures form a type-II band alignment, which is in favor of improving the efficiency of photocatalytic activity. 45 In addition, there have been several BPbased and SiH-based heterostructures, including BP/ BlueP, 46,47 BP/MX 2 , 48 SiH/graphene 49 and SiH/Al(Ga)As. 50,51 However, a BP/SiH heterostructure formed from a combination of BP and SiH monolayers has not yet been constructed or investigated.…”
Section: Introductionmentioning
confidence: 99%